Peran Blue Diplomacy Indonesia dalam Konservasi Terumbu Karang di Segitiga Terumbu Karang (CTI) pada Tahun 2024- 2025 - Azizah Fathiyyatul Fauji; Haura Nafisa Rachman; Shofianty Dewy; Syalwa Fadila Natasya; Diyah Pitaloka Rizki (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study aims to analyze Indonesia's role and contribution within the framework of the Coral Triangle Initiative on Coral Reefs, Fisheries, and Food Security (CTI-CFF) as a form of blue diplomacy in coral reef conservation efforts in the Coral Triangle region. The research method used is a qualitative approach with data collection techniques through literature studies, analysis of official CTI-CFF documents, Indonesian government policies, and reports from relevant international organizations. The data were analyzed descriptively and analytically using the perspectives of environmental diplomacy and regional cooperation. The results showed that Indonesia played a strategic role as a key country in the CTI-CFF through regional policy-making initiatives, the strengthening and expansion of marine conservation areas, increased research cooperation and scientific data exchange, and active diplomacy in various international forums related to marine issues and climate change. The implementation of Indonesia's blue diplomacy is also reflected in multi-stakeholder collaboration involving coastal communities, international institutions, the private sector, and the use of technology to support sustainable coral reef ecosystem management.